Exploring the impact of lighting sources on walking behavior in obstructed walkways among older adults - Yue Luo; Yuhao Chen; Gaojian Huang; Boyi Hu (Experimental Gerontology)
The pandemic has reinforced older adults' reliance on their homes and the concept of “aging in place”. Changes like reduced physical strength and cognitive deficit, however, have heightened the challenge of simple tasks like obstacle crossing among older adults, let alone when older adults cannot perceive the surroundings well during the nighttime. The study is, therefore, to evaluate the impact of lighting on older adults' obstacle-crossing behavior during the nighttime. Twenty-seven older adults (81 ± 6 yrs., 171 ± 12 cm, 75 ± 20 kg, 14 females) were recruited. Participants were asked to cross over the obstacle in a dark residential environment under point or line light. We found that the line light tended to (1) induce more external rotation of the trailing hip (p = 0.037) and more internal rotation of the leading ankle (p < 0.001) at leading leg liftoff; and (2) result in a more upright and erect posture during stance phase (less hip flexion, p = 0.006) and swing phase of the trailing leg (reduced pelvic flexion, p = 0.038). Postural changes induced by line light demonstrated improved body control, highlighting the influence of spatial information (horizontal & vertical directions) on crossing behavior in dark environments. The findings can provide additional evidence for the design of light systems in both retirement communities and individual homes. This is particularly important when designing built environments for the aging population, in cases where the surroundings may pose challenges such as obstructed walking, and other complex floor conditions.